أثر استراتيجية المقهى العالمي في التحصيل عند طلبة الصف الثاني المتوسط في مادة الاجتماعيات - الخزعلي، علاء إبراهيم سرحان; عمران، إسراء علي (الجمعية العلمية للدراسات التربوية المستدامة, 2024)
يهدف البحث الحالي للتعرف على (أثر استراتيجية المقهى العالمي في التحصيل عند طلبة الصف الثاني المتوسط في مادة الاجتماعيات) ولتحقيق هدف الدراسة صيغت الفرضية الصفرية الآتية لا يوجد فرق ذو دلالة إحصائية عند مستوى دلالة (0.05) بين متوسط درجات طلبة المجموعة التجريبية اللذين يدرسون باستراتيجية المقهى العالمي وبين متوسط درجات طلبة المجموعة الضابطة اللذين يدرسون بالطريقة الاعتيادية في الاختبار التحصيلي في مادة الاجتماعيات حيث تألف مجتمع البحث من طلبة الصف الثاني المتوسط في المدارس المتوسطة التابعة لمديرية تربية القادسية للعام الدراسي (۲۰۲۳-2024) وتم اختيار (ثانوية البلاغ المبين المختلطة) قصديا، واستعملت الباحثة التصميم التجريبي للمجموعتين (الضابطة- التجريبية) من ذوات الضبط الجزئي والاختبار البعدي لتحصيل، واختيرت الشعبتان (ب-ج) بطريقة عشوائية لتمثل مجموع العينة التي تكونت من (٦٤) طالب وطالبة بواقع (۳۲) للمجموعة الضابطة الذين درسوا بالطريقة الاعتيادية، حيث بلغت المجموعة التجريبية (۳۲) طالب وطالبة، الذين درسوا على وفق استراتيجية المقهى العالمي وكافأت الباحثة المجموعتين إحصائيا في متغيرات (العمر الزمني للطلبة محسوب بالشهور، اختبار الذكاء، التحصيل السابق، تحصيل الوالدين). وأعدت الباحثة الخطط التدريسية الملائمة لمجموعتي البحث وكذلك اختبار تحصيلي بعدي مكون من (٤٠) فقرة موزعة على سؤالين الأول يتكون من (٣٥) فقرة من نوع الاختيار من متعدد، ولكل فقرة أربع بدائل، والسؤال الثاني من نوع الاختبارات المقالية المكون من (٥) فقرات، وقد تم اختبار الطلبة بالاختبار التحصيلي في نهاية التجربة وبعدها أظهرت النتائج تفوق طلبة المجموعة التجريبية اللذين درسوا باستخدام استراتيجية المقهى العالمي على طلبة المجموعة الضابطة اللذين درسوا بالطريقة الاعتيادية في اختبار التحصيل لمادة الاجتماعيات وكذلك هناك أثر إيجابي كبير لاستراتيجية المقهى العالمي على تحصيل مادة الاجتماعيات لدى طلبة الصف الثاني المتوسط. The current research aims to identify (the effect of the international café strategy on the achievement of second-year intermediate students in social studies). To achieve the goal of the study, the following null hypothesis was formulated. There is no statistically significant difference at the significance level (0.05) between the average grades of the experimental group students who study with the café strategy. Global and the average grades of the control group students who study in the usual way in the achievement test in social studies, where the research population consisted of second-year intermediate students in the middle schools affiliated with the Al Qadisiyah Education Directorate for the academic year (2023-2024) and (Al-Balagh Al-Mubin Mixed Secondary School) was chosen intentionally, The researcher used an experimental design for two groups (control-experimental) with partial control and a post-test for achievement, and the two groups (B-C) were chosen randomly to represent the total sample, which consisted of (64) male and female students, with (32) for the control group who studied in the usual way, where The experimental group consisted of (32) male and female students, who studied according to the Global Café strategy, and the researcher rewarded the two groups statistically in variables (the chronological age of the students calculated in months, intelligence test, previous achievement, and parents' achievement). The researcher prepared appropriate teaching plans for the two research groups, as well as a post achievement test consisting of (40) items divided into two questions. The first consists of (35) multiple-choice type items, with four alternatives for each item, and the second question is an essay type test consisting of (5) items. The students were tested with an achievement test at the end of the experiment, after which the results showed that the students of the experimental group who studied using the Global Café strategy excelled over the students of the control group who studied using the usual method in the achievement test for the social subject. There is also a significant positive impact of the Global Café strategy on the achievement of the social subject among the students. Second intermediate grade.
Keywords: الاستراتيجيات التعليمية -- مادة الاجتماعيات -- التحصيل الدراسي -- طلبة المرحلة الثانوية